American Association for the Surgery of Trauma emergency general surgery guideline summaries 2018: acute appendicitis, acute cholecystitis, acute diverticulitis, acute pancreatitis, and small bowel obstruction. Issue 1 (27th March 2019) - Schuster, Kevin M; Holena, Daniel N; Salim, Ali; Savage, Stephanie; Crandall, Marie
Abstract : In April 2017, the American Association for the Surgery of Trauma (AAST) asked the AAST Patient Assessment Committee to undertake a gap analysis for published clinical practice guidelines in emergency general surgery (EGS). Committee members performed literature searches to catalogue published guidelines for common EGS diseases and also to identify gaps in the literature where guidelines could be created. For five of the most common EGS conditions, acute appendicitis, acute cholecystitis, acute diverticulitis, acute pancreatitis, and small bowel obstruction, we found multiple well-referenced guidelines published by leading professional organizations. We have summarized guideline recommendations for each of these disease states stratified by the AAST EGS anatomic severity score based on these published consensus guidelines. These summaries could be used to help inform evidence-based clinical decision-making, but are intended to be flexible and updatable in real time as further research emerges. Comprehensive guidelines were available for all of the diseases queried and identified gaps most commonly represented areas lacking a solid evidence base. These are therefore areas where further research is needed.